Design and Implementation of an Automatic Control System using Motors and Control Sensors to Stabilize a Horizontal Platform with a LiDAR Sensor - Taquía Gutiérrez, José Antonio (2022)
Laser imaging detection and ranging (LiDAR) sensors can be used in numerous applications mainly due to their ability to measure distances or perform 3D surface mappings. However, to perform these functions efficiently in certain situations, such as in a moving vehicle, LiDAR sensors require a stabilizing platform to prevent terrain irregularities from affecting their measurements. Moreover, accurate platform control is one of the main challenges of modern control engineering. Although several approaches concerning this challenge have been proposed, the high computational cost of control algorithms continues to be their largest drawback. Within this context, the present work seeks to implement a control system to achieve the horizontal stabilization of a two-degree-of-freedom platform for a LiDAR sensor using inertial systems and embedded software platforms, thereby guaranteeing not only portability but also low computational costs.